Examining the effect of common nitrosating agents on chitosan using a glucosamine oligosaccharide model system. (1st January 2019) - Allison, Christopher L.; Lutzke, Alec; Reynolds, Melissa M.
Highlights: Chitosan is chemically degraded by exposure to certain nitrosating protocols. Degradation is likely to proceed through the rearrangement of glucosamine units. NO itself does not detectably affect glucosamine units in the absence of oxygen. The degradation products are identified by various spectroscopic techniques. Abstract: Chitosan has received substantial attention as a biomaterial due to its unique properties. It has become increasingly common to derivatize chitosan to produce nitric oxide (NO)-releasing materials that exert various therapeutic effects through the action of NO. It is generally the case that these NO-releasing polymers are prepared by exposure to high-pressure NO or nitrosating agents like nitrous acid (HNO2 ) or alkyl nitrites (RONO). In our study, mass spectrometry and spectroscopic methods demonstrate that both monomeric and oligomeric glucosamine experience chemical alteration after exposure to HNO2 -based nitrosating conditions from the literature. In polymeric chitosan, HNO2 -based nitrosating conditions were found to induce degradation through the formation of 2, 5-anhydro-d -mannose and oligosaccharides. In contrast, the RONO tert -butyl nitrite and high-pressure NO were not found to significantly degrade or otherwise alter the structure of glucosamine or its oligomers, supporting the suitability of these approaches.